The BRICS Nations Framework for Curbing Carbon Emissions: Evidence From Energy Intensity, Renewable Energy, and Environmental Policy - Xuying Zhu; Hadi Hussain; Song Fang (Asia & the Pacific Policy Studies)
ABSTRACT In the pursuit of sustainable development, the escalating challenges of global environmental pollution and the imperative to mitigate energy intensity stand as paramount concerns. As a result, this study aims to construct a comprehensive framework that acknowledges the interplay between energy intensity, the stringency of environmental policies, and the integration of renewable energy within BRICS nations. Utilizing a panel dataset covering the years 1991–2021, this study employs a range of econometric methods such as cross‐sectional dependence tests, second‐generation unit root tests, and panel co‐integration analysis. The results reveal the pivotal roles of energy intensity, the integration of renewable energy sources, and the enforcement of stringent environmental policies in mitigating carbon emissions. Additional analysis indicates that the impact of energy intensity in lowering carbon emissions is strengthened when institutional quality and research and development capabilities reach a certain threshold, thereby offsetting the impact of openness. In accordance, the present study suggests adopting a versatile and inclusive policy approach to effectively decrease carbon emissions, providing insights for policymakers in crafting climate change mitigation strategies and fostering sustainable development.